Long‐term use of occlusal appliance has impact on sleep structure. (18th June 2014) - Sjoholm, T.; Kauko, T.; Kemppainen, P.; Rauhala, E.
Summary Acrylic occlusal appliances (OAs) have been used for temporomandibular disorders and sleep bruxism, but the effects of the treatment are still insufficiently evaluated. Two all‐night polysomnographic recordings were made in a sleep laboratory on 14 bruxists (9 females and 5 males with mean age of 27·5 years). The measurement included basic polysomnography with additional masseter muscle electromyogram and movement recording (static charge‐sensitive bed method) using randomisation. The base night recording was followed by the second study night after 8 weeks regular use of OA. The OA was made on the occlusal surface of the teeth of the upper jaw, and it was used at night time during the study period. With the OA, rapid eye movement sleep changed from 23·3% to 19·6% (P = 0·078), and slow wave sleep increased significantly from 10·2% to 14·7% (P = 0·039). Masseter contraction (MC) episodes occurred with similar frequency (9·7 vs. 10·5 episodes per hour, P = 0·272). The intensity of the rhythmic MC bursts within an episode decreased from 5·5 to 4·4 (P = 0·027). The groups were post hoc divided into responders and non‐responders using a 20% change in MC episode per hour as a cut‐off point. The results indicated that 43% of bruxists increased activity (negative responders), while 36% decreased (positive responders), and in 21%, there was no change in the level. It is concluded that OA does not have significant feedback inhibition on masseter muscle motor activity during sleep. However, OA may increase slow wave sleep.